2019
DOI: 10.1142/s0217984919502282
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of unsteady cavitating flows with RANS and DES models

Abstract: Unsteady cavitating flow with high Reynolds number and significant instability commonly exists in fluid machinery and engineering system. The high-resolution approaches, such as direct numerical simulation and large eddy simulation, are not practical for engineering issues due to the significant cost in the computational resource. The objective of this paper is to provide the approach with Detached-Eddy Simulation (DES) model based on the Reynolds-averaged Navier–Stokes (RANS) equations for predicting unsteady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…They found that both LES and DES perform well and have better agreement with the experimental results. The fact that DES predicts cavitating flow better than the URANS is also reported in several other works (Huang et al , 2012; Maasch et al , 2015; Tian et al , 2019; Usta and Korkut, 2018).…”
Section: Introductionsupporting
confidence: 77%
“…They found that both LES and DES perform well and have better agreement with the experimental results. The fact that DES predicts cavitating flow better than the URANS is also reported in several other works (Huang et al , 2012; Maasch et al , 2015; Tian et al , 2019; Usta and Korkut, 2018).…”
Section: Introductionsupporting
confidence: 77%
“…Then, the LES errors can be obtained. In summary, based on the previous research [20,23,25,36] on LES V&V, the value of r between 1 and 2 is more appropriate. Too large a value of r will make the computation capacity insufficient, while a smaller ratio will make it difficult to distinguish the LES and iteration errors.…”
Section: Application Of Vandv Approach In Waterjet Pumpmentioning
confidence: 99%
“…By combining the momentum equations for the gas phase and the liquid phase, the momentum equation for the mixture can be created, which has the following form [27]:…”
Section: Momentum Equationmentioning
confidence: 99%